2019
DOI: 10.15866/iree.v14i3.17263
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Power Transmission: State of the Art and Perspectives

Abstract: This paper deals with Wireless Power Transmission (WPT), and its main futuristic application, Space-based Solar Power (SSP). In the first part, the decisive role played by physicist Nikola TESLA in the development of electricity industry, his major concrete contributions, and his prophetic intuitions concerning wireless power are presented. The basics of the physics of the domain are also recalled. In the second part, the main experiments led until now in the domain of WPT are presented, as well as the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In fact, it has been found that radiated electromagnetic radio frequency energy (EM-RF) harvesting can be one of promising alternatives to obtain energy to power wireless sensors without dependence on environmental parameters like wind flow, temperature gradient, sun, etc. [12][13][14][15][16][17][18][19]. In this direction, researchers have developed the radiated EM-RF energy harvesting systems, which are composed by antenna, impedance matching circuit, rectifier, and the energy storage device or load [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been found that radiated electromagnetic radio frequency energy (EM-RF) harvesting can be one of promising alternatives to obtain energy to power wireless sensors without dependence on environmental parameters like wind flow, temperature gradient, sun, etc. [12][13][14][15][16][17][18][19]. In this direction, researchers have developed the radiated EM-RF energy harvesting systems, which are composed by antenna, impedance matching circuit, rectifier, and the energy storage device or load [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%